Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.addbeh.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Resolving an identity crisis: Implicit drinking identity and implicit alcohol identity are related but not the same

Abstract: Two variations of the Implicit Association Test (IAT), the Drinking Identity IAT and the Alcohol Identity IAT, assess implicit associations held in memory between one’s identity and alcohol-related constructs. Both have been shown to predict numerous drinking outcomes, but these IATs have never been directly compared to one another. The purpose of this study was to compare these IATs and evaluate their incremental predictive validity. US undergraduate students (N = 64, 50% female, mean age = 21.98 years) compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Future studies could include more questions for each construct because other aspects of evaluation and self-identification might be of importance. For example, previous studies have shown that the extent to which individuals identify themselves with addictive behavior (e.g., viewing oneself as a drinker) also strongly relates to substance use (e.g., Ramirez, Olin, & Lindgren, 2017 ). Second, the current study samples consisted exclusively of students.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could include more questions for each construct because other aspects of evaluation and self-identification might be of importance. For example, previous studies have shown that the extent to which individuals identify themselves with addictive behavior (e.g., viewing oneself as a drinker) also strongly relates to substance use (e.g., Ramirez, Olin, & Lindgren, 2017 ). Second, the current study samples consisted exclusively of students.…”
Section: Discussionmentioning
confidence: 99%
“…On the role of (implicit) drinking self-identity in alcohol use and problematic drinking: A comparison of five measures Drinking self-identity (Ramirez, Olin, & Lindgren, 2017) is an emergent, effective predictor of problematic consumption, with some work suggesting that self-identity may mediate changes in drinking behaviour over time (Blevins et al, 2018). Simultaneously, researchers have utilized implicit measures (i.e., measures which capture responses made quickly, without awareness, or unintentionally; see De Houwer, 2006) due to findings suggesting they may account for variance in alcohol consumption beyond that accounted for by traditional self-report measures (AKA explicit measures; Gray et al, 2011;Davies et al, 2017; but see Schimmack, 2019, for criticisms of implicit measures).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also identified an association between pro-drinking social norms and both alcohol use and alcohol-related problems (Larimer et al , 2004; Mattern and Neighbors, 2004; Neighbors et al , 2004; Rehm et al , 2015). A study suggested that social drinking is positively associated with problematic drinking (Ramirez et al ., 2017). Scholars have argued that a person's actions are strongly influenced by the perceptions of others regarding appropriate action in a social context (Mollen et al , 2013).…”
Section: Introductionmentioning
confidence: 99%